Chiral Modification of the Pd(111) Surface By Small Organic Molecules - (:unkn) unknown (My University, 2015)
Chiral modification of a metal surface is one of the most successful approaches of achieving enantioselective catalysis in heterogeneous phase. In this approach, an active metal surface is directly modified by adsorption of a chiral molecule (chiral modifier), the metal is responsible for catalytic activity while the adsorbed modifier controls the stereochemistry of adsorption and subsequent reactions through substrate interactions. So far, there are three types of widely recognized metal/modifier catalytic systems: tartaric acid modified Ni catalysts for the hydrogenation of β-ketoesters, cinchona modified Pt catalysts for hydrogenation of α-ketoesters and Pd catalysts modified with cinchona for selective activated alkene where high activity and enantiomeric excess is gained in comparison to the unmodified surfaces. However, the exact manner in which chirality is bestowed to a metal surface and how that affects a chiral reaction is not well understood and warrants the development of model studies (surface science analysis on well-defined single crystal surfaces under ultrahigh vacuum conditions). These model studies and surface science analysis are necessary to promote the fundamental understanding and to facilitate the rational design of a suitable metal/modifier system which is the principal focus of this dissertation. This dissertation is primarily focused on two aspects. First, a number of complementary surface science studies have been performed to characterize four different chiral modifiers: D-alanine, (S,S) tartaric acid, L-aspartic acid and α-(1-naphthyl) ethylamine on a Pd(111) surface to gain insight into the way in which they impart chirality to the surface. Second, the enantioselectivity of the chirally modified surfaces has been measured in ultrahigh vacuum. This has been achieved by exposing the modified surface to both enantiomers of another chiral molecule (the probe), to see if there is any enantiospecific interaction between the modifier and the probe. The enantioselectivity is measured from the enantioselectivity ratio which is the ratio of relative coverages of two enantiomers of the probe on a surface modified with a single enantiomer of the modifier. Combined experimental results and theoretical density functional theory calculations suggest that the amino acid modifiers impart chirality to the Pd(111) surface by an ensemble mechanism where they work collectively to form discrete chiral templates which interact with the chiral probe propylene oxide and glycidol enantiospecifically whereas, tartaric acid and naphthylethylamine provide individual chiral motifs which interact with the probes in a one to one fashion.